2022
DOI: 10.12793/tcp.2022.30.e20
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the systemic exposure and lung concentration of nafamostat using physiologically-based pharmacokinetic modeling

Abstract: Nafamostat has been actively studied for its neuroprotective activity and effect on various indications, such as coronavirus disease 2019 (COVID-19). Nafamostat has low water solubility at a specific pH and is rapidly metabolized in the blood. Therefore, it is administered only intravenously, and its distribution is not well known. The main purposes of this study are to predict and evaluate the pharmacokinetic (PK) profiles of nafamostat in a virtual healthy population under various dosing regimens. The most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This paper presents how this approach was used to identify potential new therapeutic agents for an emerging infectious disease during a public health emergency when access to clinical populations was limited and urgent solutions were required. During the COVID‐19 pandemic, PBPK modeling was applied to evaluate potential drug repurposing candidates, including the accumulation of drug into ELF and lung mass, similar to the current evaluation 38,42,43,46–50 . Notably, PBPK modeling findings were informative in the clinical development of remdesivir 42,50 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This paper presents how this approach was used to identify potential new therapeutic agents for an emerging infectious disease during a public health emergency when access to clinical populations was limited and urgent solutions were required. During the COVID‐19 pandemic, PBPK modeling was applied to evaluate potential drug repurposing candidates, including the accumulation of drug into ELF and lung mass, similar to the current evaluation 38,42,43,46–50 . Notably, PBPK modeling findings were informative in the clinical development of remdesivir 42,50 …”
Section: Discussionmentioning
confidence: 96%
“…During the COVID‐19 pandemic, PBPK modeling was applied to evaluate potential drug repurposing candidates, including the accumulation of drug into ELF and lung mass, similar to the current evaluation. 38 , 42 , 43 , 46 , 47 , 48 , 49 , 50 Notably, PBPK modeling findings were informative in the clinical development of remdesivir. 42 , 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, other TMPRSS2-targeted therapies have been tested, such as nafamostat mesylate and bromhexine. In vitro, Nafamostat resulted effective in preventing viral entrance [9,[29][30][31]. Despite the efficacy achieved in a preclinical setting [30], animal and clinical studies are limited and some other works disconfirmed its efficacy [32,33].…”
Section: Tmprss2-targeting Therapiesmentioning
confidence: 99%
“…The parameters with high sensitivity are considered the key factors that should be accurately controlled to improve the prediction accuracy of the models. Jeong et al [103] used a PBTK approach, coupled with global sensitivity analysis, to predict and evaluate the pharmacokinetic profiles of nafamostat in a virtual healthy population under various dosing regimens, and the results suggested that the hepatic distribution and metabolism had a significant impact on systemic exposure and clearance of nafamostat.…”
Section: Sensitivity Analysismentioning
confidence: 99%